2014
DOI: 10.1007/s00221-014-3898-9
|View full text |Cite
|
Sign up to set email alerts
|

Integration of vestibular and gastrointestinal inputs by cerebellar fastigial nucleus neurons: multisensory influences on motion sickness

Abstract: Previous studies demonstrated that ingestion of the emetic compound copper sulfate (CuSO4) alters the responses to vestibular stimulation of a large fraction of neurons in brainstem regions that mediate nausea and vomiting, thereby affecting motion sickness susceptibility. Other studies suggested that the processing of vestibular inputs by cerebellar neurons plays a critical role in generating motion sickness, and that neurons in the cerebellar fastigial nucleus receive visceral inputs. These findings raised t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…This review found that vomiting almost always occurred in the presence of vertigo in a variety of space occupying lesions. The cause of vomiting may be due to lesion-related pressure effects on the area postrema in the caudal aspect of the floor for the fourth ventricle ( 33 ), or related to affectation of cerebellar and brainstem pathways involved in the integration of vestibular and non-vestibular afferents relating to body position in space ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…This review found that vomiting almost always occurred in the presence of vertigo in a variety of space occupying lesions. The cause of vomiting may be due to lesion-related pressure effects on the area postrema in the caudal aspect of the floor for the fourth ventricle ( 33 ), or related to affectation of cerebellar and brainstem pathways involved in the integration of vestibular and non-vestibular afferents relating to body position in space ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such responses are due to convergence of vestibular inputs with different spatial and temporal characteristics, and are thus referred to as spatiotemporal convergence (STC) responses (Schor and Angelaki 1992; Moy et al 2012). STC responses have previously been reported to be common amongst rFN neurons in the decerebrate cat (Catanzaro et al 2014). Twenty percent of rFN neurons (1/5) with directional encoding of hindlimb movement had STC responses, whereas 67% of rFN neurons (8/12) without directional encoding had STC responses.…”
Section: Resultsmentioning
confidence: 91%
“…For example, responses could be different if the limb movement was self-generated instead of passive. Furthermore, differences in preparation sometimes have significant effects on the behavior of neural networks, such that the same stimulus will elicit different responses if the animal is decerebrate or conscious (Destefino et al 2011; Catanzaro et al 2014). Therefore, follow-up studies in conscious animals, which incorporate both active and passive hindlimb movements, should shed light on how hindlimb movements are processed by rFN neurons, and may provide further insights regarding the relevance of these signals in postural control.…”
Section: Discussionmentioning
confidence: 99%
“…PONV is one of the complex entities in anaesthesia. Its pathophysiology involves various receptors and afferent pathways, in which the primary ones are the stimulation of vagal mucosal pathway of the gastrointestinal system by paracrine activity, the stimulation of the chemoreceptor trigger zone (CTZ) [14], the vestibular system [15], area postrema of the midbrain [16] and afferent pathways from the cerebral cortex. Inhibition of any of these pathways would prevent transmission of impulses to the nucleus tracts solitarius (NTS), thus avoiding emesis.…”
Section: Discussionmentioning
confidence: 99%